Misfit dislocations nucleated from the surface in strained-layer heterostructures - Zou, J; Cockayne, D (1996)
The nucleation of misfit dislocations from the surface in strained-layer heterostructures is considered theoretically, When the interface between the epitaxial layer and the substrate is included, the model suggested by Matthews and his co-workers needs to be modified.